2017
DOI: 10.1016/j.bbrep.2017.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Aldehyde dehydrogenase with acetaminophen as examined by spectroscopies and molecular docking

Abstract: The interaction of acetaminophen, a non-substrate anionic ligand, with Aldehyde Dehydrogenase was studied by fluorescence, UV–Vis absorption, and circular dichroism spectroscopies under simulated physiological conditions. The fluorescence spectra and data generated showed that acetaminophen binding to ALDH is purely dynamic quenching mechanism. The acetaminophen-ALDH is kinetically rapid reversible interaction with a binding constant, Ka, of 4.91×103 L mol−1. There was an existence of second binding site of AL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 57 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…This result is consistent with the experimental work of Courade et al, who showed that paracetamol in concentration of up to 100 mM had no effect on MAO(A) activity. 34 Kolawole showed experimentally and via docking simulations that paracetamol does bind to ALDH, 39 and in fact, our work also shows that both paracetamol and NAPQI should be competitive inhibitors for ALDH, with EBEs stronger than natural substrates DOPAL and homovanilin. Inhibition of ALDH may thus cause a shift in equilibrium, which would indirectly inhibit MAO.…”
Section: Potential Inhibition Of the Biosynthesis Of Dopaminementioning
confidence: 99%
“…This result is consistent with the experimental work of Courade et al, who showed that paracetamol in concentration of up to 100 mM had no effect on MAO(A) activity. 34 Kolawole showed experimentally and via docking simulations that paracetamol does bind to ALDH, 39 and in fact, our work also shows that both paracetamol and NAPQI should be competitive inhibitors for ALDH, with EBEs stronger than natural substrates DOPAL and homovanilin. Inhibition of ALDH may thus cause a shift in equilibrium, which would indirectly inhibit MAO.…”
Section: Potential Inhibition Of the Biosynthesis Of Dopaminementioning
confidence: 99%
“…Few reports have been published discussing the molecular docking of aldehyde dehydrogenases to different substrates showing similar binding energy. For instance, the docking of aldehyde dehydrogenase to an aromatic drug, acetaminophen, into its hydrophobic cavity involving isoleucine, phenylalanine, arginine, leucine, glutamic acid, and glutamine via hydrogen and Van der Waals bonding showed quite similar binding energy (−5.3 kcal mol −1 ) 66 . Although, aldehyde dehydrogenases have well‐established involvement in polyaromatic hydrocarbons, studies specifically concentrated on PAD involvement in styrene metabolism are still emerging 67 …”
Section: Resultsmentioning
confidence: 99%